2020
DOI: 10.1038/s41467-020-18535-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of uniform carbon nitride layers with extended optical absorption towards efficient water-splitting photoanodes

Abstract: A general synthesis of carbon nitride (CN) films with extended optical absorption, excellent charge separation under illumination, and outstanding performance as a photoanode in water-splitting photoelectrochemical cells is reported. To this end, we introduced a universal method to rapidly grow CN monomers directly from a hot saturated solution on various substrates. Upon calcination, a highly uniform carbon nitride layer with tuned structural and photophysical properties and in intimate contact with the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 52 publications
3
111
1
Order By: Relevance
“…Although PCN‐promoted water photooxidation was sometimes suggested, solely on the basis of recorded photocurrents, to occur in some studies, it has typically not been supported by direct experimental evidence of oxygen evolution [14b,c,33] . In addition, it has been shown that it was primarily the photocorrosion that was responsible for high photocurrents as only small amount of oxygen could be detected in the absence of electron donors and/or the faradaic efficiency for oxygen formation was that low to suggest that other PEC reactions, such as oxidation of PCN itself, were occurring [14e,34] . Therefore, we assume that photocurrents observed at PCN‐based photoanodes in aqueous electrolytes in the absence of any additional electron donors are mostly due to photocorrosion, leading to the formation of nitrates [35] or partially oxidized heptazine or triazine species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PCN‐promoted water photooxidation was sometimes suggested, solely on the basis of recorded photocurrents, to occur in some studies, it has typically not been supported by direct experimental evidence of oxygen evolution [14b,c,33] . In addition, it has been shown that it was primarily the photocorrosion that was responsible for high photocurrents as only small amount of oxygen could be detected in the absence of electron donors and/or the faradaic efficiency for oxygen formation was that low to suggest that other PEC reactions, such as oxidation of PCN itself, were occurring [14e,34] . Therefore, we assume that photocurrents observed at PCN‐based photoanodes in aqueous electrolytes in the absence of any additional electron donors are mostly due to photocorrosion, leading to the formation of nitrates [35] or partially oxidized heptazine or triazine species.…”
Section: Resultsmentioning
confidence: 99%
“…Since PCN itself was not soluble in any of the tested organic solvents, its precursors were used to grow a layer on the substrate via high‐temperature condensation, a notoriously uncontrollable process, leading to the tens of micrometers thick films composed of large loose particles. Such films typically exhibited suboptimal mechanical and photo‐operational stability, which was demonstrated by the detachment of PCN particles from the film under sonication and pronounced self‐photooxidation revealed by low faradaic efficiencies towards the reaction products [14b,e] . In order to produce processable solutions or suspensions of PCN, ultrasonication‐assisted, thermal or chemical exfoliation has been suggested [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The direct growth of g-CN layers on substrates such as fluorine-doped tin oxide (FTO) allows for effective CN-to-substrate adhesion and thus enables the improvement of electrical conductivity, charge separation, and hole extraction efficiency. [160,161] Photocurrent densities of up to 353 µA cm −2 have been achieved using g-CN/FTO photoanodes. [160] Another strategy is to modify g-CN, e.g., via surface functionalization.…”
Section: Solar Batteriesmentioning
confidence: 99%
“…In addition, the reductive coupling of aryl or alkyl halides is of great significance in modern organic synthesis [47][48][49][50][51][52][53][54][55][56] , which has prompted us to select this kind of reaction as the model reaction to make our idea come true. Encouraged by prior success in applying carbon nitride-supported transition metal (M/g-C 3 N 4 ) into photocatalytic water splitting, [57][58][59][60][61][62][63][64][65] we selected this kind of semiconductor to achieve our goals. It is worth noting that the proton reduction is desired in previous literatures related to M/g-C 3 N 4 -catalyzed water splitting, while this half-reaction would inhibit our reaction [44][45][46][57][58][59][60][61][62][63][64][65] .…”
Section: Fig 1 Coupling Organic Reactions With Photocatalytic Half-reaction Of Water Splittingmentioning
confidence: 99%
“…Encouraged by prior success in applying carbon nitride-supported transition metal (M/g-C 3 N 4 ) into photocatalytic water splitting, [57][58][59][60][61][62][63][64][65] we selected this kind of semiconductor to achieve our goals. It is worth noting that the proton reduction is desired in previous literatures related to M/g-C 3 N 4 -catalyzed water splitting, while this half-reaction would inhibit our reaction [44][45][46][57][58][59][60][61][62][63][64][65] . Therefore, the M/g-C 3 N 4 and reaction conditions had to be modified to accelerate the water oxidation and inhibit the proton reduction via a new method, and the results are herein reported.…”
Section: Fig 1 Coupling Organic Reactions With Photocatalytic Half-reaction Of Water Splittingmentioning
confidence: 99%